The An-Nahdliyah and The Yanbu'a Method in Learning to Read the Qur'an in the Vocational High School: Comparative Study - Suminto Suminto; Arinatussadiyah Arinatussadiyah (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
This research is motivated because there are still very few people who can read the Al-Qur'an with the correct recitation. Efforts must be made to conduct Al-Qur'an learning in educational institutions, both formal and informal. This paper aims to describe the implementation and implications of learning to read the Koran with an-nahdliyah and yanbu'a methods. This research uses a qualitative approach. Data analysis techniques used single case analysis and cross-case analysis. Research results: (1) The implementation of Al-Qur'an reading and writing learning with an-nahdliyah method in Nahdlatul 'Ulama Vocational High School (SMK-NU) and yanbu'a method in Islamic Vocational High School (SMKI) Al-Azhaar Tulungagung which aims so that students can read the Qur'an in accordance with the science of recitation with implementation: opening prayer, classical, private, evaluation, motivation, and closing prayer. (2) Learning material at SMK-NU: volume books (volumes 1-6), Al-Qur'an, and the book